Three Aquatic Hyphomycetes New to Kumaun Himalaya, India - Jalal, Ruchi; Bisht, Saraswati; Altaf, Saima (Indian Forester, 2024)
Aquatic hyphomycetes are the fungi with distinctive conidial shapes mostly inhabiting in dead submerged leaf litter of fresh water-bodies. Samples collected from freshwater streams and irrigation canals of Kumaun Himalayan foothill regions, were processed, incubated and observed for identification. It was interesting to isolate three species of aquatic hyphomycetes namely, Dicranidion sp. Harkness, Monacrosporium lysipagum (Drechsler) Subram and Wiesneriomyces laurinus (Tassi) Kirk as new records from Kumaun Himalaya.